Conocimientos y prácticas de fotoprotección y su asociación con el fotoenvejecimiento cutáneo en deportistas de Liga Deportiva Universitaria de Loja - Godoy Ríos, María Fernanda (2021)
"Photoprotection" is defined as all measure aimed at protecting the skin from the sun's rays, avoid the sun, the use of sunscreen, and protective clothing that is the first line of defense against photoaging, which is defined as aging premature skin resulting from prolonged and repeated exposure to solar radiation. Sunlight is essential for the synthesis of vitamin D and has beneficial effects on mood, however, ultraviolet radiation (UV) is responsible for several harmful effects both acute and chronic on human skin. The present study proposes to determine the knowledge and practices of photoprotection and its association with skin photoaging in athletes of the “Liga Deportiva Universitaria de Loja team”, period April - September 2019. For this, a quantitative methodological structure of a observational, and cross-sectional nature was designed, which was used in a sample of 125 athletes who were subjected to a survey to determine the degree of solar affectation. Consequently, it was obtained as a result that although 32% of athletes have habitual knowledge about photoprotection and 65% have inadequate sun protection habits and that there is not statistically significant relationship between sensitization and photoprotection practices to skin photoaging in the population studied. Keywords: skin photoaging, photoprotection, athletes.